OPHI and UNDP regional MPI brief. Latin America and the Caribbean: an analysis of levels and trends in the global - Oxford Poverty and Human Development Initiative (OPHI) (Oxford Poverty and Human Development Initiative (OPHI) and United Nations Development Programme (UNDP), 2022)
This report examines the most recent trends in multidimensional poverty using the global Multidimensional Poverty Index (MPI) microdata from countries in the Latin American and Caribbean (LAC) region included in the 2021 global MPI database. Trends within the global MPI and its components, i.e., the headcount ratio (H) and the intensity of poverty (A), are examined.1 Furthermore, an analysis of possible disparities across urban and rural areas and subnational regions is also presented. Examining patterns and changes in the global MPI across time seeks to uncover rich evidence, which may guide our understanding on the progress made within this region, whilst also pinpointing crucial areas where advancements are still needed.